2021
DOI: 10.1037/cep0000239
|View full text |Cite
|
Sign up to set email alerts
|

Valence does not affect serial recall.

Abstract: Despite being the prototypical test of short-term/working memory, immediate serial recall is affected by numerous lexical and long-term memory factors. Within this large literature, very few studies have examined whether performance on the task is affected by valence, the extent to which a word is viewed as positive or negative. Whereas the NEVER model (Bowen, Kark, & Kensinger, 2018) makes the general prediction that negative words will be remembered better than positive words, two previous studies using seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 34 publications
(92 reference statements)
4
32
1
Order By: Relevance
“…As Table 1 indicates, a number of previous studies have found no difference in recognition memory for positive and negative words, but the current results are based on words that are equated for more dimensions. The results are also consistent with those of Bireta et al (2021) finding no difference between serial recall of positive and negative words.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As Table 1 indicates, a number of previous studies have found no difference in recognition memory for positive and negative words, but the current results are based on words that are equated for more dimensions. The results are also consistent with those of Bireta et al (2021) finding no difference between serial recall of positive and negative words.…”
Section: Resultssupporting
confidence: 91%
“…Although Bireta et al (2021) reported results that disconfirm the predictions of the NEVER model, they tested only serial recall.…”
mentioning
confidence: 96%
“…Our results clearly establish that while valence does not impact short-term ordered recall (Bireta et al, 2021), arousal does have a reliable effect. In their discussion, Bireta et al acknowledged that they cannot dismiss the possibility that their null effect was due to their implementation of many controls in stimulus selection.…”
Section: Discussionsupporting
confidence: 72%
“…Arousal could also increase the level of activation of lexical-semantic representations due to the involvement of the motivation systems involved in emotion processing. Under this view, because they contrasted positively and negatively valence words, Bireta et al (2021) could not have uncovered an effect of valence; items in both conditions would influence activation equally. However, with a neutral condition, it should be possible to observe an effect of valence.…”
Section: Discussionmentioning
confidence: 97%
“…The early and late AoA words did differ in valence, t(26) = 2.45, p = .02, with the early words being more positive (M = 6.04, SD = 1.24) than the later words (M = 4.94, SD = 1.14), using theWarriner, Kuperman, and Brysbaert (2013) norms. However,Bireta, Guitard, Neath, and Surprenant (2021) have argued that valence does not affect immediate serial recall.…”
mentioning
confidence: 99%